2006
DOI: 10.1159/000092833
|View full text |Cite
|
Sign up to set email alerts
|

Subjective and Objective Evaluation of Noncultured Epidermal Cellular Grafting for Repigmenting Vitiligo

Abstract: Background: Noncultured epidermal cell transplantation in vitiligo permits the coverage of relatively large areas without culturing cells. Objective: To investigate the effectiveness of noncultured epidermal cell transplantation in treating stabilized vitiligo using objective and subjective evaluation methods. Methods: Noncultured autologous melanocytes and keratinocytes were grafted in a hyaluronic-acid-enriched suspension on superficially laser-abraded vitiligo lesions in 40 patients with refractory stable v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 25 publications
(16 reference statements)
1
40
0
Order By: Relevance
“…On the other hand, several studies conducted on Caucasian patients pointed out a small impairment of QoL as well [7,11,25,27,28], whereas the majority of the survey performed on patients with dark skin showed a moderate/very large impairment of QoL [12,13,14,17,18,19,22,23,28]. Two investigations conducted on selected samples of vitiligo patients candidate to use camouflage [15] and attending treatment with noncultured epidermal cellular grafting [16] showed a moderate impairment of QoL in white subjects. In studies in which a control group of healthy subjects/patients affected by other skin diseases was provided, a statistical difference between vitiligo patients and controls was shown [14,17,19].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, several studies conducted on Caucasian patients pointed out a small impairment of QoL as well [7,11,25,27,28], whereas the majority of the survey performed on patients with dark skin showed a moderate/very large impairment of QoL [12,13,14,17,18,19,22,23,28]. Two investigations conducted on selected samples of vitiligo patients candidate to use camouflage [15] and attending treatment with noncultured epidermal cellular grafting [16] showed a moderate impairment of QoL in white subjects. In studies in which a control group of healthy subjects/patients affected by other skin diseases was provided, a statistical difference between vitiligo patients and controls was shown [14,17,19].…”
Section: Discussionmentioning
confidence: 99%
“…Belhadjali et al [17] did not observe any influence of the aforesaid variable on the DLQI score in their sample. Van Geel et al [16] and Parsad et al [12] showed a significant decrease in overall DLQI scores in their patients after a successful therapy, but Kiprono et al [28] and Karelson et al [29] did not. In the present study no significant association was documented between the DLQI mean score and progression of the disease or regression of vitiligo after therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Autologous melanocyte transplantation is an option in case of disfiguring, stable vitiligo, but the optimal modality is still debated. So far, the focus has been on procedures of isolation, application and eventually cultivation using interfollicular epidermal melanocytes harvested by skin biopsy from the patient [for reviews, see [1,2,3,4,5,6]]. As for keratinocytes, a stem cell pool resides in the outer root sheath (ORS) of hair follicles also for melanocytes [7], illustrated clinically by the well-known phenomenon of follicular repigmentation in spontaneously healing vitiligo.…”
Section: Introductionmentioning
confidence: 99%
“…In many Asian cultures, vitiligo is even taken as a sign of ‘leprosy’ or ‘uncleanliness’ [10]. Repigmentation is associated with a gain in quality of life [11]. …”
Section: Introductionmentioning
confidence: 99%